Pengaruh Pemahaman Perpajakan, Kesadaran Wajib Pajak, dan Penurunan Tarif PPH Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pemilik UMKM Di Kabupaten Gresik - Marcella Islamay Ellen Erindra Putri; Tituk Diah Widajantie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test empirically the effect of understanding taxation, taxpayer awareness, and reducing pph rates on the compliance of individual taxpayers who own MSMEs in Gresik District. The type of research used is quantitative research. The sample consists of taxpayers in the Gresik Pratama KPP working area. Determination of the sample in this study using probability sampling technique, namely simple random sampling and obtained as many as 100 respondents. The data collection technique used a questionnaire. This research analysis technique uses the PLS method and is tested using the SmartPLS 4.0 program. The results of this study indicate that understanding taxation has a positive and significant effect on taxpayer compliance, taxpayer awareness has a positive and significant effect on taxpayer compliance, a decrease in pph rates has a positive and insignificant effect on taxpayer compliance.